2023
DOI: 10.1142/s0219455424500597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil–Structure Interaction on Inelastic Displacement Ratios of Bridge Structures Subjected to Pulse-Like Ground Motions

Abstract: This study aimed to investigate the effect of soil–structure interaction (SSI) on the inelastic displacement ratio of bridge structures subjected to near-fault pulse-like earthquake ground motions. SSI was modeled using a discrete-time recursive filter approach and frequency-dependent foundation–soil impedance functions. A total of 105 near-fault earthquake ground motion records were used for the analysis. The study also compared the soil–foundation–superstructure (SFS) system with a fixed-base system to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…For example, Sung Y.C. et al [13] investigated the effect of the soil-structure interaction on the inelastic displacement ratio of bridge structures subjected to near-fault pulse-like earthquake ground motions. Das S. et al [14] conducted a comparative case study of seismically vulnerable surfaces of rail-bridge piers with and without soil-structure interaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Sung Y.C. et al [13] investigated the effect of the soil-structure interaction on the inelastic displacement ratio of bridge structures subjected to near-fault pulse-like earthquake ground motions. Das S. et al [14] conducted a comparative case study of seismically vulnerable surfaces of rail-bridge piers with and without soil-structure interaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the mechanism of considering the effect of the soil-structure interaction on the seismic response of large-span bridge structures is very complex, and is closely related to the input ground vibration field characteristics [13,16,17], foundation soil properties [15,[18][19][20], and the structural form of the bridge [14,17,21]. The effect of the interaction on the structure is dependent on their relative properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation